The Influence of Sharia Financial Literacy on Interest in Saving in Sharia Banks - Dafi Andin Muhammad (Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2025)
The development of the Islamic financial industry in Indonesia shows a positive trend, butthe low level of Islamic financial literacy is one of the factors hampering public interest in usingIslamic banking services. The 2025 OJK National Survey on Financial Literacy and Inclusion(SNLIK) recorded that the level of Islamic financial literacy only reached 43.42%, far belowconventional financial literacy. This condition indicates that public understanding of the basicprinciples of Islamic economics, contract mechanisms, profit-sharing systems, and the fundamentaldifferences between Islamic and conventional banks is still uneven. Through a review of theory,previous literature, and emerging phenomena in society, this study examines the relationshipbetween Islamic financial literacy and interest in saving in Islamic banks. The results of the literaturereview indicate that a good understanding of Islamic financial concepts can increase trust,strengthen positive perceptions, and encourage public preference for Sharia-based savingsproducts. Thus, Islamic financial literacy plays a significant role in shaping interest in saving andis a strategic factor in strengthening the penetration of Islamic banking in Indonesia.